Elucidating the effect of reactor configuration on xylan recovery during reductive alkaline hydrogen peroxide pretreatment system with implications for scale-up - Nur Syahirah Ahmad Sobri; Shuhaida Harun; Wei Feng Ang; Peer Mohamed Abdul; Muhammad Zulhaziman Mat Salleh (Chemical Engineering Journal, 2026)

Temperature-sensitive chlorophyll degradation uncouples degreening from other ripening traits and guides postharvest quality improvement in kiwifruit - Ameer Hamza Hafeez; Zheng Zhang; Ang Li; Zhebin Zeng; Yan Chen; Tiantian Li; Xiaomei Ji; Yi Wang; Zhongyan Wang; Yunjiang Cheng; Hamza Sohail; Di Feng; et al. (Postharvest Biology and Technology, 2026)

Mechanistic insights into the migration and speciation evolution of N, P, K and metals during hydrothermal liquefaction of food waste: A multi-phase distribution analysis - Rui Bao; Shuzhong Wang; Jiaqi Feng; Ang Tu (Journal of Environmental Chemical Engineering, 2026)

Revealing thermoelectric property-performance correlations for the design of self-powered sensors - Zijian Lin; Bangzhou Tian; Xiaobo Tan; Chuke Zhao; Jiaxing Luo; Zhilong Zhao; Fan Feng; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2026)

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

Physical exercise protects cardiovascular fitness in long-term spaceflight: what have we learned? - Zi’ang Zhang; Wenjuan Xing; Guiling Wu; Xing Zhang; Jia Li; Yingxian Li; Feng Gao (Science China Life Sciences, 2026)

Chlorine dioxide fumigation induces transcriptomic and metabolomic reprogramming enhancing resistance to soft rot in kiwifruit - Ang Li; Shuang Luo; Di Feng; Xiaoya Chen; Zhidan Zhao; Tiantian Li; Yunhe Meng; Xiaoqin Yang; Yunjiang Cheng; Yunliu Zeng (Postharvest Biology and Technology, 2026)

The DNA-binding protein PfAP2-V regulates erythrocyte invasion and pathogenesis of the human malaria parasite Plasmodium falciparum - Yanxin Zhang; Changhong Wang; Qilong Li; Ang Li; Yutao Zhang; Ziwei Su; Liying Yu; Kexin Zheng; Tong Liu; Ning Jiang; Yiwei Zhang; Xiaoyu Sang; et al. (Science China Life Sciences, 2026)

Flash Joule carbothermal chemistry to synthesize porous silica-based ceramics for thermal safety - Feng Xu; Hongjian Zhang; Edison Huixiang Ang; Yisha Wang; Tianyang Cui; Yufei Lu; Zhentao Nie; Haoyang Wang; Wei Yang; Jixin Zhu (Chemical Engineering Journal, 2026)

A permeability model for gas-bearing coal-rock under internal stress and gas adsorption effects - Yangyang Guo; Longyong Shu; Kai Wang; Feng Du; Chao Xu; Yongbo Cai; Long Wang; Chang'ang Du (Process Safety and Environmental Protection, 2026)

Dual single sites of single metal atom and molecule ligand on TiO₂ atomic-scale step to boost photocatalytic CO2 reduction - Yuxin Liu; Yang Wang; Yibo Feng; Peixin Cui; Kaiwen Wang; Zhouhao Zhu; Xiaoyuan Zhou; Liyong Gan; Shengqi Chu; Guangcai Chang; Ang Li; Xiaodong Han; et al. (Chemical Engineering Journal, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Investigation into the mechanism of performance enhancement of solvent-based asphalt induced by microbial digestion - Ying Wang; Junyan Yi; Claudio Lantieri; Ang Li; Zhongshi Pei; Xinman Ai; Wenyi Zhou; Ke Xu; Decheng Feng (Chemical Engineering Journal, 2025)

Acetylated glucomannan-CNT scaffolds with dual-drug release promote hiPSCs-driven cortical regeneration by suppressing inflammation and anoikis - Yue Gao; Wenxi Li; Wanting Lu; Fuqiang Tang; Xian Xiao; Yinggang Li; Jiaxing Huang; Zhiqi Liang; Yuqing Wu; Yanwen Li; Qingjian Zou; Liangxue Lai; et al. (Carbohydrate Polymers, 2025)

Exposure to Aldehydes, Heterocyclic Aromatic Amines and Terpenes With Sex Hormones in U.S. Children and Adolescents: Sex-, Age-Dependent Patterns and Vitamin D Effect Modification - Yayuan Mei; Ang Li; Xinyu Wang; Hui Xu; Guoshuang Feng (Phenomics, 2025)

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

New insights into the interaction between nanocolloid of graphene oxide and dissolved organic matter: Spectroscopic methods and density functional theory calculations - Ang Liu; Tuantuan Fan; Weibo Zhang; Xihuan Wang; Zhong Jin; Zeya Zhang; Peng Xia; Fei Guo; Chenglian Feng; Yingchen Bai (Journal of Hazardous Materials, 2025)

Impacts of synoptic weather patterns on Hefei's ozone in warm season and analysis of transport pathways during extreme pollution events - Feng Hu; Pinhua Xie; Jin Xu; Ang Li; Yinsheng Lv; Zhidong Zhang; Jiangyi Zheng; Xin Tian (Journal of Environmental Sciences, 2025)

A patient-friendly sprayable rapid gelation powder (SRGP) with prolonged mucoadhesion for oral ulcer therapy - Jingyi Liu; Songbai Zhang; Jinteng Feng; Zhe Feng; Min Zhang; Ang Li; Feng Xu; Haoyu Wang; Dandan Pei; Yuanbo Jia (Chemical Engineering Journal, 2025)

Cerium oxide nanoparticles as potent inhibitors of ferroptosis: role of antioxidant activity and protein regulation - Chenran Feng; Tong Yang; Jie Zhou; Chen Wang; Zheng Chu; Ying Zhang; Junzhe Zhang; Yin Kwan Wong; Cui Liu; Peng Gao; Ang Ma; Huan Tang; et al. (Journal of Molecular Medicine, 2025)

Targeting myeloid differentiation protein 2 ameliorates rheumatoid arthritis by inhibiting inflammation and ferroptosis via MAPK and NF-κB signaling pathways - Lirun Zhou; Tong Yang; Shujie Zhang; Dandan Liu; Chenran Feng; Jiang Ni; Qiaoli Shi; Yanqing Liu; Yuqing Meng; Yongping Zhu; Huan Tang; Jigang Wang; et al. (Journal of Molecular Medicine, 2025)

Vertical characteristics of bacterial community and the interaction of dissolved organic matter in sediments of a shallow lake, China - Xihuan Wang; Weibo Zhang; Ang Liu; Zhong Jin; Yili Fan; Zeya Zhang; Chenglian Feng; Yingchen Bai (Journal of Environmental Chemical Engineering, 2025)

Inorganic and organic constituent analysis: A data fusion strategy to differentiate between wines of different origins - Yingyue Su; Zhaoxiang Wang; Qianqian Liu; Yuyu Li; Cui Zhang; Xiaohui Feng; Ang Zhang; Chunlong Yuan (Food Control, 2025)

Molecular detection and genotyping of bovine viral diarrhea virus in four provinces of China - Ying Liu; Feng Zhou; Xuan-ang Wang; Xi-Meng Chen; Lan-Lan Zheng; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Spatial-temporal distribution and emission of urban scale air pollutants in Hefei based on Mobile-DOAS - Zhidong Zhang; Pinhua Xie; Ang Li; Min Qin; Jin Xu; Zhaokun Hu; Xin Tian; Feng Hu; Yinsheng Lv; Jiangyi Zheng; Youtao Li (Journal of Environmental Sciences, 2025)

Dynamic interactions between Fe, Mn, S and C cycles in the Okinawa Trough seep sediments - Cuiling Xu; Qing Li; Taiheng Lv; Zhilei Sun; Ang Li; Ye Chen; Xilin Zhang; Feng Cai; Nengyou Wu (Global and Planetary Change, 2025)

Photothermal halloysite nanotube hybrids with CoO/carbon layers for enhanced pollutant degradation and solar-powered water purification - Yifang Zhang; Hongyao Zhao; Jiayi Zhou; Yanyun Wang; Yangping Zhang; Jialing Shen; Danhong Shang; Feng Zeng; Jianming Pan; Yiyan Song; Fu Yang; Edison Huixiang Ang (Desalination, 2025)

Investigations of spatial-temporal distribution and regional transport in typical section of NO2 in eastern China using Mobile-DOAS - Zhidong Zhang; Pinhua Xie; Ang Li; Jin Xu; Xin Tian; Feng Hu; Zhaokun Hu; Yinsheng Lv; Youtao Li; Qiang Zhang; Wenqing Liu (Science of The Total Environment, 2025)

Correction: Exposure to Aldehydes, Heterocyclic Aromatic Amines and Terpenes with Sex Hormones in U.S. Children and Adolescents: Sex-, Age-Dependent Patterns and Vitamin D Effect Modification - Yayuan Mei; Ang Li; Xinyu Wang; Hui Xu; Guoshuang Feng (Phenomics, 2025)

Deciphering structure-rheological properties relationship via the studies of 11 s-rich and 7 s-rich soy protein isolate - Binyu Luan; Ang Meng; Wenjing Zhang; Fengqiujie Wang; Feng Liu; Weichun Pan; Xiuqing Zhu; Bo Zhang (Food Chemistry, 2025)

Integrated metabolomic and transcriptomic analysis reveals the regulatory effects of IAA on polyphenol biosynthesis and antioxidant activity in Phlebopus portentosus - Taobo Xiang; Feng Ge; Lei Zhu; Gaige Shao; Tao Wu; Hao Fan; Yueqian Liu; Longyu Wang; Jing Wang; Peng Li; Qin He; Ailiang Jiang; et al. (Food Bioscience, 2025)

Temperature effects on nitrogen removal and N2O emissions in anammox reactors - Xiaolong Yu; Fumitake Nishimura; Taira Hidaka; Zi-ang Du; Feng Wang (Bioresource Technology, 2025)

Effects of Ammonia loading and oxygen flux on nitrogen removal in a PNA-coupled MABR - Jiang-Feng Zhang; Jinfeng Bao; Chun-Yu Lai; Chen Zhou; Ang Li; He-Ping Zhao (Journal of Water Process Engineering, 2025)

Deciphering the code of temperature rise on aerobic granular sludge stability: A DSF-c-di-GMP mediated regulatory mechanism - Aiqi Tang; Chunyan Li; Donglei Feng; Ang Li (Environmental Research, 2025)

Roles of lncRNA in the crosstalk between osteogenesis and angiogenesis in the bone microenvironment - Shihua Zhang; Jianmin Guo; Yuting He; Zhi’ang Su; Yao Feng; Lan Zhang; Jun Zou; Xiquan Weng; Yu Yuan (Journal of Zhejiang University-SCIENCE B, 2025)

Methane emissions from the riverine sandy wetlands on the Mongolia Plateau - Ang Li; Zun-Lan Luo; Katerina Machacova; Song Zhao; Jin-Chao Feng; Xing-Guo Han; Zhi-Ping Wang (Environmental Monitoring and Assessment, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Boosted photocatalytic H2O2 production in pure water with amino-modified N, S-doped carbon dots - Haoyuan Qin; Lei Sun; Suchang Zou; Ang Bian; Yanhua Cui; Jianhua Hou; Changyu Lu; Chunsheng Li; Feng Guo; Weilong Shi (Chemical Engineering Journal, 2024)

Behavior of surface loaded clay foundation reinforced by GESCs with lateral geosynthetic cushion under freeze-thaw cycles - Zi-Ang Gu; Jian-Feng Chen; Chungsik Yoo (Geotextiles and Geomembranes, 2024)

Probabilistic evaluation method for the stability of large underground cavern considering the uncertainty of rock mass mechanical parameters: A case study of Baihetan underground powerhouse project - Guofeng Liu; Chi Zhou; Kun Feng; Quan Jiang; Shengfeng Li; Han Bao; Ang Li (Engineering Geology, 2024)

Enhanced Daily Reference Evapotranspiration Estimation Using Optimized Hybrid Support Vector Regression Models - Stephen Luo Sheng Yong; Jing Lin Ng; Yuk Feng Huang; Chun Kit Ang; Norashikin Ahmad Kamal; Majid Mirzaei; Ali Najah Ahmed (Water Resources Management, 2024)

Behavior of geosynthetic-encased stone column reinforced foundation under freeze-thaw cycles - Zi-Ang Gu; Chungsik Yoo; Jian-Feng Chen (Geotextiles and Geomembranes, 2024)

Efficient synthesis of quaternary piezo-photonic materials for pressure visualization and E-signature anti-counterfeiting - Jiaren Du; Tengyue Wang; Yukun Li; Puxian Xiong; Yao Xiao; Ang Feng; Xiaomeng Wang; Kai Jiang; Hengwei Lin (Chemical Engineering Journal, 2024)

Ultrafast hot electron transfer and trap-state mediated charge separation for boosted photothermal-assisted photocatalytic H2 evolution - Hao Yuan; Haoyuan Qin; Kaiqu Sun; Xinhai Sun; Jialin Lu; Ang Bian; Jianhua Hou; Changyu Lu; Chunsheng Li; Feng Guo; Weilong Shi (Chemical Engineering Journal, 2024)

Dynamic Mechanical Response and Fracture Characteristics of Multi-flawed Rocks Exposed to Hydrostatic Confinements - Wei You; Feng Dai; Yi Liu; Ang Li (Rock Mechanics and Rock Engineering, 2024)

A CNN-SVR model for NO2 profile prediction based on MAX-DOAS observations: The influence of Chinese New Year overlapping the 2020 COVID-19 lockdown on vertical distributions of tropospheric NO2 in Nanjing, China - Xin Tian; Zijie Wang; Pinhua Xie; Jin Xu; Ang Li; Yifeng Pan; Feng Hu; Zhaokun Hu; Mingsheng Chen; Jiangyi Zheng (Journal of Environmental Sciences, 2024)

New formula of vegetation roughness height and Darcy–Weisbach friction factor in channel flow - Da-Qian Feng; Jing-Jing Fan; Wei-Jie Wang; Cheng-Xing Xia; Ang Li (Journal of Hydrology, 2024)

Quantitative prediction of surrounding rock deformation via an energy-based damage model combining with microseismic monitoring - Dingran Song; Yi Liu; Feng Dai; Ruochen Jiang; Ang Li (Tunnelling and Underground Space Technology, 2024)

Lateral migration of methane at a cold seep: Evidence from U–Th dating of methane-derived authigenic carbonate in the Middle Okinawa Trough - Ang Li; Nengyou Wu; Zhifeng Wan; Qing Li; Zhilei Sun; Feng Cai; Dong Feng (Marine and Petroleum Geology, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

An AI-powered approach to improving tunnel blast performance considering geological conditions - Yaosheng Liu; Ang Li; Feng Dai; Ruochen Jiang; Yi Liu; Rui Chen (Tunnelling and Underground Space Technology, 2024)

Influence of methane seep activities and sea-level changes on elemental and isotopic compositions and abundance of carbonates in sediments of the Okinawa Trough since the last glacial period - Qing Li; Hongbin Wang; Feng Cai; Di Luo; Fanxing Kong; Ang Li; Xiting Liu (Journal of Asian Earth Sciences, 2024)

Centrifuge investigation on behavior of geosynthetic-encased stone column supported embankment under freeze-thaw cycles - Zi-Ang Gu; Fu-Jun Niu; Jian-Feng Chen; Chungsik Yoo (Geotextiles and Geomembranes, 2024)

Deep learning to obtain high-throughput morphological phenotypes and its genetic correlation with swimming performance in juvenile large yellow croaker - Junjia Zeng; Miaosheng Feng; Yacheng Deng; Pengxin Jiang; Yinlin Bai; Jiaying Wang; Ang Qu; Wei Liu; Zhou Jiang; Qian He; Zhijun Wang; Peng Xu (Aquaculture, 2024)

Integrated analysis of the transport process and source attribution of an extreme ozone pollution event in Hefei at different vertical heights: A case of study - Feng Hu; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Aurelia Lupaşcu; Tim Butler; Zhaokun Hu; YinSheng Lv; ZhiDong Zhang; Jiangyi Zheng (Science of The Total Environment, 2024)

Identification and characterization of a novel Iflavirus in a stored-product psocid, Liposcelis bostrychophila (Psocodea: Liposcelididae) - Peng-Yu Guo; Dan-Dan Wei; Hua-Yue Feng; Xin-Ping Tang; Yu-Ang Chen; Yi Li; Jin-Jun Wang (Journal of Stored Products Research, 2023)

Investigation of filtration performance and phosphorus removal in an electric field controlled dynamic membrane bioreactor - Long Chen; Miao Lv; Yang-Cheng Ding; Zi-Ang Lv; Dan-Na Ding; Di Wu; Haiping Yuan; Nanwen Zhu; Hua-Jun Feng (Chemical Engineering Journal, 2023)

McPrA - A new gas profile inversion algorithm for MAX-DOAS and apply to 50 m vertical resolution - Jiangyi Zheng; Pinhua Xie; Xin Tian; Jin Xu; Ang Li; Bo Ren; Feng Hu; Zhaokun Hu; Yinsheng Lv; Zhidong Zhang; Wenqing Liu (Science of The Total Environment, 2023)

Removal of chloramphenicol and resistance gene changes in electric-integrated vertical flow constructed wetlands - Yuran Feng; Ailijiang Nuerla; Menghan Tian; Anwar Mamat; Ang Si; Jiali Chang; Mukadasi Abudureheman; Chaoyue He; Jinjin Zhu; Zhaohong Tong; Zhaojiang Liu (Journal of Environmental Management, 2023)

Cooperation of carbon doping and carbon loading boosts photocatalytic activity by the optimum photo-induced electron trapping and interfacial charge transfer - Hao Yuan; Haoran Sun; Yuxing Shi; Jiaxuan Wang; Ang Bian; Youyou Hu; Feng Guo; Weilong Shi; Xin Du; Zhenhui Kang (Chemical Engineering Journal, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Failure mechanism of underwater shield tunnel: An experimental and theoretical study - Kun Liang; Kun Feng; Li Zhang; Chuan He; Ang Su; Wenqi Guo (Tunnelling and Underground Space Technology, 2023)

Dynamic Responses and Failure Behaviors of Saturated Rocks Subjected to Repetitive Compression–Shear Impacting - Hongbo Du; Feng Dai; Ang Li; Ruochen Jiang (Rock Mechanics and Rock Engineering, 2023)

Intracellular electron competition in response to the oxygen pressure of the aerobic denitrification process in an O2-based membrane biofilm reactor (MBfR) for nitrate removal - Liang Feng; Fei-yun Sun; Jixian Yang; Di Cui; Zuo-hua Li; Shanshan Pi; He-Ping Zhao; Ang Li (Science of The Total Environment, 2023)

Enhanced ultrasound-assisted pore-adjustable spherical imma-Fe3O4 catalytic-activated piezoelectric Fenton reaction for PDE-5i degradation - Zi-ang Jia; Qing-rui Zeng; Xun Zhang; Wei Feng (Journal of Environmental Chemical Engineering, 2023)

Comparison of alive and dead benthic foraminiferal fauna off the Changjiang Estuary: Understanding water-mass properties and taphonomic processes - Feng Jiang; Daidu Fan; Quanhong Zhao; Yijing Wu; Fahui Ren; Yan Liu; Ang Li (Frontiers in Marine Science, 2023)
Benthic foraminifera (BF) are utilized in palaeo-environmental reconstruction based on our understanding of how living individuals respond to environmental variations. However, there is still a lack of empirical insight into how non-environmental factors, such as taphonomic processes, influence the preservations of fossil BF in strata. In this study, we compare the spatial distribution and composition of alive and dead BF fauna in surface sediments to elucidate how well fossil foraminiferal fauna mirror quasi-contemporary alive BF groups indicative of different water masses off a mega-river (Changjiang) estuary, which is characterized by intense and complex river-sea interactions. On-site measurements of bottom water salinity, temperature, and dissolved oxygen were conducted in the summer to determine water mass properties. A same-site comparison of alive (Rose Bengal stained) and dead foraminiferal fauna in surface sediment samples over 73 stations was then carried out. Q-mode Hierarchical clustering analysis was used to differentiate foraminiferal assemblages based on the relative abundance of common species. Three distinct regions with different water-mass properties were identified. The distribution pattern of dead foraminiferal fauna is mainly inherited from alive fauna, while the density and diversity of the dead fauna were found to be higher than those of the alive one. Both alive and dead fauna were clustered into four assemblages. A few common alive species (small-agglutinated and thin-calcareous) were rarely found in dead fauna, and a few common dead species (preferring low temperature and indicating allochthonous sources) were rarely present in alive fauna. The alive foraminiferal abundance and diversity were mainly determined by food resources and environmental properties of salinity and temperature. Alive foraminiferal assemblages were separated by different water masses determined by river-sea interactions off the Changjiang Estuary. The “time-averaging” effect was found to be responsible for the higher density and diversity of the dead fauna. Disintegration of agglutinated tests, dissolution of calcareous tests and selective transportation were observed to contribute to the different species compositions between the alive and dead fauna. Nevertheless, indicative species-environment relations in alive and taphocoenose fauna were found to be almost homologous among most common species. This suggests that distinct benthic foraminiferal assemblages can be used to effectively differentiate between different water masses in the study coastal seas.

Characterization and shifting of microbial community to denitrification for anaerobic sulfamethoxazole biodegradation with different electron acceptors - Xiaoli Su; Feiyun Sun; Jianjun Zhang; Dingyu Xing; Xiaoying Li; Zi Song; Liang Feng; Zhichao Huang; Ang Li (Journal of Cleaner Production, 2023)

Low-temperature-resistance granulation of activated sludge and the microbial responses to the granular structural stabilization - Chunyan Yuan; Feiyun Sun; Jianjun Zhang; Liang Feng; Honghua Tu; Ang Li (Chemosphere, 2023)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Genome-wide CRISPR activation screen identifies candidate receptors for SARS-CoV-2 entry - Shiyou Zhu; Ying Liu; Zhuo Zhou; Zhiying Zhang; Xia Xiao; Zhiheng Liu; Ang Chen; Xiaojing Dong; Feng Tian; Shihua Chen; Yiyuan Xu; Chunhui Wang; et al. (Science China Life Sciences, 2022)

The association between urine elements and fasting glucose levels in a community-based elderly people in Beijing - Liu Liu; Ang Li; Qun Xu; Qin Wang; Feng Han; Chunyu Xu; Zhe Liu; Dongqun Xu; Donggang Xu (Environmental Science and Pollution Research, 2022)

Influences of Loading Method and Notch Type on Rock Fracture Toughness Measurements: From the Perspectives of T-Stress and Fracture Process Zone - Mingdong Wei; Feng Dai; Yi Liu; Ang Li; Zelin Yan (Rock Mechanics and Rock Engineering, 2021)

Numerical Analysis of the Water-blocking Performance of a Floor with a Composite Structure under Fluid–solid Coupling - Ang Li; Qian Mu; Li Ma; Chaoyang Liu; Shengquan Wang; Feng Wang; Lin Mou (Mine Water and the Environment, 2021)

Frequency Characteristics of Acoustic Emissions Induced by Crack Propagation in Rock Tensile Fracture - Ruochen Jiang; Feng Dai; Yi Liu; Ang Li; Peng Feng (Rock Mechanics and Rock Engineering, 2021)

Dynamic Compression–Shear Response and Failure Criterion of Rocks with Hydrostatic Confining Pressure: An Experimental Investigation - Hongbo Du; Feng Dai; Mingdong Wei; Ang Li; Zelin Yan (Rock Mechanics and Rock Engineering, 2021)

Improving Education About Breast Cancer for Medical Students in China - Ang Zheng; Xinmiao Yu; Lijuan Fan; Jinfei Ma; Feng Jin (Journal of Cancer Education, 2020)

Litorilituus lipolyticus sp. nov., isolated from intertidal sand of the Yellow Sea in China, and emended description of Colwellia asteriadis - Ang Liu; Yan-Jiao Zhang; Qing-Jie Xue; Hui Wang; Yuan-Yuan Yang; Feng Du; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2020)

Effects of osmotic stress on Na+/K+-ATPase, caspase 3/7 activity, and the expression profiling of sirt1, hsf1, and hsp70 in the roughskin sculpin (Trachidermus fasciatus) - Qian Ma; JieHua Kuang; Xinfu Liu; Ang Li; Wenrong Feng; Zhimeng Zhuang (Fish Physiology and Biochemistry, 2020)

Flavivirga rizhaonensis sp. nov., a marine bacterium isolated from intertidal sand - Ang Liu; Hong-Mei Liu; Feng Du; Shuang Wang; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Qing-Jie Xue; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2019)

Analysis of a Complex Flexural Toppling Failure of Large Underground Caverns in Layered Rock Masses - Ang Li; Feng Dai; Nuwen Xu; Gongkai Gu; Zhonghua Hu (Rock Mechanics and Rock Engineering, 2019)

Proteomics analysis of Schwann cell-derived exosomes: a novel therapeutic strategy for central nervous system injury - Zhijian Wei; Baoyou Fan; Han Ding; Yang Liu; Haoshuai Tang; Dayu Pan; Jiaxiao Shi; Pengyuan Zheng; Hongyu Shi; Heng Wu; Ang Li; Shiqing Feng (Molecular and Cellular Biochemistry, 2019)

Disruption of bone morphogenetic protein type IA receptor in osteoblasts impairs bone quality and bone strength in mice - Quanwei Bao; Ang Li; Sixu Chen; Jianquan Feng; Huayu Liu; Hao Qin; Junfeng Li; Daocheng Liu; Yue Shen; Zhaowen Zong (Cell and Tissue Research, 2018)

Relative Permeability of Gas for Unconventional Reservoirs - Ang Liu; Kai Wang; Jie Zang; Feng Du; Aitao Zhou (Transport in Porous Media, 2018)

Analysis of the sucrose synthase gene family in tobacco: structure, phylogeny, and expression patterns - Zhong Wang; Pan Wei; Mingzhu Wu; Yalong Xu; Feng Li; Zhaopeng Luo; Jianfeng Zhang; Ang Chen; Xiaodong Xie; Peijian Cao; Fucheng Lin; Jun Yang (Planta, 2015)

Tree‐ring‐based temperature reconstruction for the northern Greater Higgnan Mountains, China, since A.D. 1717 - Tongwen Zhang; Yujiang Yuan; Wenshou Wei; Shulong Yu; Ruibo Zhang; Huaming Shang; Feng Chen; Zi'ang Fan; Li Qin (International Journal of Climatology, 2013)
In this paper, ring‐width chronologies of pine trees ( Pinus sylvestris var. mongolica ) from one sampling site in the northern Greater Higgnan Mountains, China, were constructed. The results of growth‐climate responses show that mean temperature is the limiting factor affecting radial growth of pine trees in the study area. Consequently, mean temperature from May to October from 1717 to 2008 has been reconstructed using the standard chronology. For the calibrated period (1957‐2008), the explained variance of the reconstruction is 57%. The characteristics of the reconstruction expose that mean temperature has increased since the 1970s, and the decade 2000s and 1990s are also ranked as the warm decades on record. However, this period from 1970s to now is not exceptional within the past 300 years. By applying an 11‐year moving average to the reconstruction, three warm periods and three cold periods are evident. The warm and cold periods of the reconstructed mean temperature correspond well with other reconstructions. Power spectral and wavelet analysis demonstrated the existence of significant ∼70‐ and ∼100‐year cycles of variability. Furthermore, the reconstruction and North Atlantic Oscillation Index showed a significant positive correlation ( r = 0.34, n = 136, p

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Study on algorithms of low SNR inversion of T 2 spectrum in NMR - Feng Lin; Zhu-Wen Wang; Jing-Ye Li; Xue-Ang Zhang; Yu-Long Jiang (Applied Geophysics, 2011)

Environmental significance of RSL in ancient city wall: historical desertification of Ordos Plateau, Northern China - Yinzhou Huang; Nai-ang Wang; Tonghui He; Hongyi Chen; Wenyong Feng; Hao Long (Climatic Change, 2009)